2013
DOI: 10.1007/s00404-013-2852-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral evening primrose oil on menopausal hot flashes: a randomized clinical trial

Abstract: The application of oral evening primrose oil compared with placebo for controlling hot flashes may decrease more the intensity of attacks as well as ameliorating the HFRDIS score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…In a trial on effect of evening primrose oil on hot flashes, frequency of hot flash decreased from 5.2±1.9 to 3.2±1.8 in the evening primrose and from 5.4±1.9 to 3.7±20 in placebo group ( 27 ). The severity of hot flash reduction was greater than placebo group, but, the difference between groups was not significant (p=0.23).…”
Section: Resultsmentioning
confidence: 99%
“…In a trial on effect of evening primrose oil on hot flashes, frequency of hot flash decreased from 5.2±1.9 to 3.2±1.8 in the evening primrose and from 5.4±1.9 to 3.7±20 in placebo group ( 27 ). The severity of hot flash reduction was greater than placebo group, but, the difference between groups was not significant (p=0.23).…”
Section: Resultsmentioning
confidence: 99%
“…17 ). In a randomized placebo-controlled clinical trial (56 menopausal women), a significant improvement in the severity of menopausal hot flashes was reported in the evening primrose (500 mg/day, 6 weeks) group ( Farzaneh et al, 2013 ). A systematic review of evening primrose oil for menopausal symptoms suggests that although the herb is well tolerated, efficacy is not clinically significant ( Bayles and Usatine, 2009 ).…”
Section: Botanicals Used By Menopausal Womenmentioning
confidence: 99%
“…Additionally, EPR oil was considered to reduce the severity of cyclical mastalgia, a state that is caused mainly by hormonal imbalance in premenopausal women (93). Oral administration of EPR oil was also reported to have an effect against menopausal hot flashes (94). In addition, one study demonstrated that dietary-EPR oil modifies the nociceptive reaction and symptoms accompanying intermittent cold stress and reduces inflammation (88).…”
Section: Discussionmentioning
confidence: 99%